Game and Simulation Stimulate Conceptual Change about Molecular Emergence in Different Ways, with Potential Cultural Implications - Andrea Gauthier (Education Sciences, 2024)
Many undergraduate students hold robust misconceptions about the emergent nature of molecular processes, believing them to be directed rather than random. Interactive simulations might help transform such misconceptions by visualizing stochastic processes in a time-independent medium and enabling students to manipulate the environment to test their naïve hypotheses. Furthermore, game-based learning (GBL) might enhance the effectiveness of such simulations by promoting productive negativity (PN), i.e., learning from failure. In a randomized controlled trial with pre-test, post-test and delayed one-year follow-up, undergraduates (n = 84) engaged with either a GBL or interactive simulation (SIM) environment for 20–45 min and were compared to a baseline group (n = 138). GBL (p = 0.035) and SIM (p = 0.069) resolved more misconceptions than baseline but did not differ from each other (p = 0.992). GBL group also trended toward more positive long-term conceptual change. In-game interactions generated in response to PN were predictive of conceptual change in the GBL group alone, suggesting that PN may only be effective when supported by game design. Participants’ native English-speaking status had a moderating effect, with native-speakers performing well in GBL and poorly in SIM environment, while the opposite was true for non-native-speakers, which, as discussed herein, may be aligned with cultural differences in acceptability of GBL. The GBL intervention generated longer voluntary use (p = 0.005), especially amongst frequent game-players. The results inform how GBL/SIM approaches can implement PN as a mechanism for conceptual change about molecular emergence.